Consistent measures of oxidative balance predict survival but not reproduction in a long‐distance migrant. Issue 8 (28th April 2020) - Bodey, Thomas W.; Cleasby, Ian R.; Blount, Jonathan D.; McElwaine, Graham; Vigfusdottir, Freydis; Bearhop, Stuart
Abstract: Physiological processes, including those that disrupt oxidative balance, have been proposed as key to understanding fundamental life‐history trade‐offs. Yet, examination of changes in oxidative balance within wild animals across time, space and major life‐history challenges remains uncommon. For example, migration presents substantial physiological challenges for individuals, and data on migratory individuals would provide crucial context for exposing the importance of relationships between oxidative balance and fitness outcomes. Here we examined the consistency of commonly used measures of oxidative balance in longitudinally sampled free‐living individuals of a long‐lived, long‐distance migrant, the Brent goose Branta bernicla hrota over periods of months to years. Although inter‐individual and temporal variation in measures of oxidative balance were substantial, we found high consistency in measures of lipid peroxidation and circulating non‐enzymatic antioxidants in longitudinally sampled individuals. This suggests the potential for the existence of individual oxidative phenotypes. Given intra‐individual consistency, we then examined how these physiological measures relate to survival and reproductive success across all sampled individuals. Surprisingly, lower survival was predicted for individuals with lower levels of damage, with no measured physiological metric associated with reproductive success. Our results demonstrate that snapshot measurements of a consistent measure of oxidative balance can inform our understanding of differences in a key demographic trait. However, the positive relationship between oxidative damage and survival emphasises the need to investigate the relationships between the oxidative system and fitness outcomes in other species undergoing similar physiologically challenging life cycles. This would highlight the extent to which variation in such traits and resource allocation trade‐offs is a result of adaptation to different life‐history strategies. Abstract : Studies in wild animals are key for revealing life‐history trade‐offs involving physiological processes. The authors demonstrate in individuals undertaking one of the longest waterfowl migrations that: measurements of oxidative state are consistent across months or years, identify the presence of 'oxidative phenotypes', and link measurements to survival in an unconstrained wild system.